Correlation between anxiety and depression risk and atopic dermatitis severity in Taiwan: A cross-sectional studyCapsule Summary - Chia-Jung Hsu, MD; Dereck Shen, PhD; Tom C. Chan, MD, PhD; Yung-Tsu Cho, MD; Chao-Hsiun Tang, PhD; Chia-Yu Chu, MD, PhD (Elsevier, 2022)
Background: Limited studies on atopic dermatitis (AD) have investigated the possible covariance of sociodemographic factors with the Hospital Anxiety and Depression Scale (HADS). Objective: This study aimed to examine the possible covariance between AD severity and HADS scores of patients in Taiwan. Methods: Patients with AD from a medical center and 2 regional hospitals in Taiwan were enrolled in this cross-sectional study from April 2018 to April 2019. AD severity was measured using the "scoring atopic dermatitis" index, and anxiety and depression were screened based on HADS. Results: A total of 200 patients were included. After correcting for sociodemographic variables, significantly more borderline (≥8) and abnormal (≥11) cases of anxiety/depression (P < .05) were noted in patients with moderate-to-severe AD. Limitations: First, the cross-sectional study design cannot show causality. Second, baseline data, including a history of underlying cancer or previous psychiatric disorder, were not obtained in the questionnaire and may confound the HADS scores. Finally, a standardized psychiatric clinical interviews study design should be used for higher accuracy in the assessment of psycho-comorbidities. Conclusion: Higher anxiety and depression risks were noted in patients with moderate-to-severe AD. Except for psychosomatic symptoms, all kinds of anxiety and depression symptoms occurred more frequently in patients with moderate-to-severe AD.